2012
DOI: 10.1182/blood-2011-02-339556
|View full text |Cite
|
Sign up to set email alerts
|

Nodal marginal zone lymphoma: gene expression and miRNA profiling identify diagnostic markers and potential therapeutic targets

Abstract: Nodal marginal zone lymphoma (NMZL) is a small B-cell neoplasm whose molecular pathogenesis is still essentially unknown and whose differentiation from other small B-cell lymphomas is hampered by the lack of specific markers. We have analyzed gene expression, miRNA profile, and copy number data from 15 NMZL cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 38 publications
5
66
0
1
Order By: Relevance
“…These findings confirm the similarity of splenic marginal zone lymphoma with the marginal zone. 12,[24][25][26] As already described in other low-grade lymphomas, 16 the inflammatory cytokines present in the microenvironment may be involved in the onset and progression of disease contributing to the survival of tumor cells, consistently with what is already known about the role of the inflammatory microenvironment in this lymphoma type.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These findings confirm the similarity of splenic marginal zone lymphoma with the marginal zone. 12,[24][25][26] As already described in other low-grade lymphomas, 16 the inflammatory cytokines present in the microenvironment may be involved in the onset and progression of disease contributing to the survival of tumor cells, consistently with what is already known about the role of the inflammatory microenvironment in this lymphoma type.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, among the miRNAs with increased expression in nodal marginal zone lymphoma were several already known to be overexpressed in this lymphoma type, such as miR199a 16 (Table 2; Supplementary Table 5). …”
Section: Comparison Between Splenic and Nodal Marginal Zone Lymphomasmentioning
confidence: 95%
See 1 more Smart Citation
“…73 Another study of 15 NMZLs and 16 FLs reported a rather homogeneous gene expression profile in NMZLs resembling marginal zone and memory B cells. 90 Compared to FL, NMZL showed overexpression of NF-κB-related and -binding genes (TRAF4, CD82), IL-32, histones, members of the TNF family (TACI, TNFRSF14), and genes involved in lymphocyte activation (TGFB1). FLs showed higher expression of germinal center markers (CD10, BCL6, GCET1, LMO2) in comparison to NMZL.…”
Section: Molecular Featuresmentioning
confidence: 99%
“…51,52 The expression program of marginal zone lymphomas shows that nodal and extranodal types share common profiles with upregulation of genes related to cell-cell and cell-extracellular matrix interactions. 53,54 Peripheral T-cell lymphomas. GEP studies in T-cell lymphomas have been able to recognize specific global expression patterns for the most common entities although they are more difficult to interpret, due to the lower frequency of these tumors and the heterogeneity of the tumor cell microenvironment.…”
Section: Characterization Of Known Entities and Recognition Of New Camentioning
confidence: 99%